Roles of Membrane and Vesicular Traffic in Regulation of the Hippo Pathway - Verghese, Shilpi; Moberg, Ken (Frontiers in Cell and Developmental Biology, 2020)
The Hippo pathway is a well conserved signaling cascade that modulates cell proliferation and survival in response to external cues such as cell:cell contact, injury, and nutritional status. Our understanding of the Hippo pathway has evolved from a series of genetic interactions defined in the fruit fly Drosophila melanogaster into a complex series of biochemical mechanisms in which transmembrane and cytoskeletal proteins modulate cytoplasmic phosphatase and kinase activities that converge on the serine/threonine kinase Warts (Wts). This pathway is well conserved in human cells and broadly implicated in cancer. Progress in understanding biochemistry of the Hippo pathway highlights a need for improved understanding of the cell biological contexts in which this biochemistry occurs. A significant body of data linking Drosophila Hippo signaling to membranes and membrane traffic raise the possibility that some of these biochemical events occur on the cytoplasmic face of vesicles. The Yki-endosome link was solidified by discoveries that cytoplasmic Yki concentrates at late-endosomes and physically interacts with two endosomal adaptor proteins, Myopic and Leash. These two proteins escort Yki through the endolysosomal pathway and are required for Yki lysosomal turnover. Molecules involved recruiting and tethering Yki along this endosomal route are not defined, but are predicted to play key roles in regulating Yki levels and thus Hippo-responsiveness of cells. As Wts is recruited to the apical membrane by upstream Hippo components, endosomal internalization could also affect complexes involved in Yki phosphorylation. Very recent work has revealed an unexpected, non-transcriptional role of membrane-associated Yki in triggering actinomyosin contractility via the myosin-regulatory light chain Spaghetti squash (Sqh). How Yki interacts with the membrane and controls Sqh is unclear, but this mechanism represents a novel regulatory step based on induced localization of Yki to a specific membrane compartment. These and other data will be discussed as we review data linking Yki to membrane and vesicular traffic in development and homeostasis.